Calculation of Rainwater Harvesting: A Case Study of Çorum City - Murat Dağ; Murat Ay (Doğal Afetler ve Çevre Dergisi)
This study includes the importance of harvesting rainwater, which is a hydrological variable, and its ability to be used as an alternative to existing water resources, its storage function against drought, as well as the analysis of the benefits and harms of rainwater. In this context, the rainwater potential that can be collected on the roof of the AHL Park Shopping Center, which is approximately 27000 m2, located in the Central district of Çorum Province, was calculated, its cost was evaluated in today's economic conditions, and recommendations were made. Considering the high initial investment and labour costs, the long depreciation period of the system (50-100 years), and the troublesome, costly and risky construction of the system in such buildings whose construction has been completed, it has been observed that the possibility of implementing the system is low probability in our country. However, it can be said that such reasons are weaker than the risks such as drought danger and quality water shortage that threaten living creatures. On the other hand, other more efficient and economical alternative storage systems can be developed and rainwater harvesting systems can be integrated with different water harvesting systems (e.g. groundwater). A more detailed regulation on rainwater harvesting is needed in our country, and it is recommended to use the regulations from countries such as Germany and England in order to make a calculation and estimation.